Avaliação financeira do processo de transplantes de fígado em Minas Gerais: um estudo do diálogo entre o custeio baseado em atividades e a teoria das restrições - Heloisa Azevedo Drumond (2014)
This research study aims to present the dialogue between two methods of management:Activity Based Costing (ABC) and the Theory of Constraints (TOC). The adopted empirical basis the process of liver transplantation in Minas Gerais, with financial support in a study involving the application of the two methods. The unit of analysis of this research includes the MG Transplantation (MGTX), linked to the Hospital Foundation of Minas Gerais (FHEMIG), and agents. The objective is to examine the implementation of the two methods, identify convergent and divergent points and analyze the results. The strategy applied research was an exploratory study using bibliographic studies, field exploration and use of free to capture relevant points cognition research. The main technique used was the focused group also interviews, analysis of various secondary data and technical visits. The application of research showed that the bond between the two technologies is the mapping process which enables to understand costs as metadata, or data information. ABC technology allows for the mapping of processes, with in-depth treatment of the steps and constitutive activity. For each activity took place costing and setting attributes. The results showed that each activity in their independence, may contain factors of success or failure of management factors. However, according to TOC, a great location does not correspond to a global optimum. Thus, working stints in each activity can mean an individual does not reflect the efficiency and scope of managerial efficiency in the whole process. The technology allows the TOC to work the undesirable effects of the institution, in order to identify the one that stands out, that is the biggest constraint to achieve the goal. Soon after its identification, the restriction will be crafted to achieve the whole process and be overcome, and a new restriction will arise and go through the same process. The simultaneous use of TOC and ABC technology produces better results than the use of either separately. ABC Technology enables better understanding of the process as the process mapping and summarization capabilities, while TOC technology strengthens these results to undesirable effects, in order to act and evaluate the impact can be identified that will generate the process.